+0  
 
0
112
1
avatar

Solve (x - 1)^2 - 4*|x - 1| + 3 = 0.

 Feb 18, 2021
 #1
avatar+120287 
+1

Assuming  x  is  real.......

 

Note  that   4 l x  - 1l     can be written as   4sqrt  [ (x -1)^2   ]

 

So  we  have  that

 

(x  -1)^2  - 4sqrt [ (x - 1)^2 ]  +  3   =    0

 

(x - 1)^2  + 3  =    4sqrt [ (x - 1)^2 ]           square  both sides

 

(x - 1)^4   + 6 (x-1)^2    + 9   =   16 (x - 1)^2

 

(x - 1)^4  - 10(x - 1)^2  + 9   =  0

 

Let  (x  -1)^2   =    a.......so we have

 

a^2  - 10a  +  9  =  0         factor

 

(a - 9)  ( a  - 1)  = 0

 

Set  each  factor to 0  and  solve  for a

 

So

 

a  = 9        or          a   = 1

 

So

 

(x  -1)^2  = 9                   or        ( x  -1)^2    =   1        take  both roots

 

x - 1  = 3         x  - 1  =  -3              x  -1      =  1         x  -1  =  -1

 

x = 4                 x =  -2                   x  =  2                    x  =  0

 

 

cool cool cool

 Feb 18, 2021

18 Online Users

avatar
avatar